Soroprevalência e manifestações da Toxoplasmose ocular em pacientes com Esquizofrenia - Morais, Fabio Barreto [UNIFESP] (2019)
Objectives: To investigate the seroprevalence of Toxoplasma gondii and perform ophthalmic examination in patients with schizophrenia and controls to identify lesions suggestive of ocular toxoplasmosis. Questionnaire on risk factors for toxoplasmosis was applied. Methods: Thirty-four patients with schizophrenia and 85 healthy controls were submitted to serology for toxoplasmosis and ophthalmologic examination. A questionnaire was applied to evaluate contact with cats, presence of cats in the region, filtered water consumption, consumption of undercooked meat, contact with sand tanks, bathing in rivers, schooling and family income. Results: Patients with schizophrenia had a higher prevalence of IgG positive than controls (91.18% [95% confidence interval (CI), 77.04%−96.95%] vs. 70.59% [95% CI, 60.18%−79.21%], p = 0.017). One (3%) schizophrenic patient and two (2.4%) controls presented fundoscopic scarring. The schizophrenia group showed contact with the absent cat, with little and a lot respectively in 20 (58.8%), 4 (11.8%), 10 (29.4%); the control, in 25 (29.4%), 45 (52.9%), 15 (17.6%). In the schizophrenia group, the presence of cats in the region was absent, little and much respectively in 4 (11.8%), 15 (44.1%), 15 (44.1%); in the control group, in 10 (11.8%), 35 (41.2%), 40 (47%). In the schizophrenia group, the consumption of filtered water was never, sometimes and always respectively in 9 (26.5%), 20 (58.8%), 5 (14.7%); in the control group, in 35 (41.2%), 45 (52.9%), 5 (5.9%). In the schizophrenia group, the consumption of malted meat was never, at times and frequently respectively in 20 (58.8%), 12 (35.3%), 2 (5.9%); in the control group, in 50 (58.8%), 30 (35.3%), 5 (5.9%). In the schizophrenia group, contact with sand tanks was never, at times and frequently respectively in 5 (14.7%), 20 (58.8%), 9 (26.5%); in the control group, in 25 (29.4%), 40 (47.1%), 20 (23.5%). In the schizophrenia group, the habit of river baths was never, sometimes and frequently respectively in 18 (52.9%), 14 (41.2%), 2 (5.9%); in the control group, in 41 (48.2%), 40 (47.1%), 4 (4.7%). In the schizophrenia group, the educational level was illiterate, incomplete high school, complete secondary education and higher education (complete or incomplete) respectively in 15 (44.1%), 17 (50.0%), 2 (5.9%), 0 (0%); in the control group, in 4 (4.8%), 44 (52.4%), 28 (33.3%), 8 (9.5%). In the schizophrenia group, the family income was in minimum wages: up to one, two to three, and more than three respectively in 11 (32.4%), 20 (58.8%), 3 (8.8); in the control group, in 11 (13.1%), 25 (29.8%), 48 (57.1%). Conclusion: Seropositivity was significantly higher in schizophrenics (p = 0.017). There was no association between fundoscopic scarring and schizophrenia (p = 1,000). There were no statistically significant differences (p ≤ 0.05) between the groups regarding contact with cats (p = 0.247), cats in the region (p = 0.832), filtered water (p = 0.058)), undercooked meat (p = 1,000), sand tanks (p = 0.219), river baths (p = 0.769). A statistically significant difference was found between the groups in relation to educational level and family income. The control group presented higher rates of family income (p < 0.001) and educational level (p < 0.001).